Effect of different defects on the polarization mechanism of (Nb,Ga) codoped TiO2 single crystals - Wang, Lei; Li, Jinsheng; Liu, Xudong; Zhang, Mu; Li, Xiaodong; Liu, Shaohong; Sun, Xudong (Ceramics international, 2023)
Various defects have a profound impact on the dielectric properties and polarization mechanisms of (Nb,Ga) codoped TiO2 crystals. However, the research conducted in this area remains limited. To address this, we grew (Nb,Ga) codoped TiO2 crystals via the Verneuil method and investigated their dielectric properties under various atmospheric annealing conditions. Annealing in oxygen reduces the number of defects. In this case, the point defects associated with oxygen vacancies is unable to fully form the ideal complex defect clusters which can form effective pegging of free electrons. On the other hand, the defects are mainly in the form of simple defect clusters that causes hopping polarization. Annealing under mixed gas (Ar:H2 = 95%:5%) increases the number of defects and contains more free carriers, which migrate to the interface between the sample and the electrode, leading to interfacial polarization. Both hopping polarization and interfacial polarization are slow polarization, resulting in an increase in dielectric loss and a decrease in frequency stability. Annealing in air or nitrogen atmospheres forms ideal defect dipole clusters, where the electron-pinned defect dipoles (EPDD) are predominantly polarized, resulting in superior dielectric properties. It has been clarified that EPDD as the main polarization form can yield better dielectric properties. By focusing on single crystals as the research subject, we effectively eliminate the influence of grain boundaries, enabling a more accurate assessment of the effects of various crystal defects on dielectric properties. This study holds substantial implications for the advancement of TiO2-based dielectric materials, offering valuable insights into their performance optimization.